Greater Care Program in the face of the challenges of aging: a qualitative analysis - Cláudio Phillipe Fernandes de Castro; Janaína de Souza Aredes; Karla Cristina Giacomin; Josélia Oliveira Araújo Firmo (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE To understand the perception of different actors involved in the older adults care process in the intersectoral strategy of the Programa Maior Cuidado (PMC - Greater Care Program), aiming at the development of actions that contribute to the improvement of the services provided. METHODS Eleven qualitative interviews guided by a semi-structured script were conducted in 2020 with key informants directly involved in the PMC: the older adults and their families, caregivers, health professionals and social assistance. In addition, to understand the functioning and proposals of the PMC, a documentary analysis was also carried out with the tracking of existing information on the guidelines, protocols, and management instruments. The content analysis technique was used to classify textual data, and the interpretation process was mediated by the theoretical-methodological framework of hermeneutic anthropology. RESULTS Two categories were identified: "Repercussions of the care offered by the PMC: the 'little' that makes a difference" and "Problems beyond the PMC: the limits of family care in the face of violence against the older adults". For all interviewees, the perception the PMC is very necessary is unison, being able to minimize the occurrence of health problems and avoid transfers of the older adults to hospitals and Long Stay Institutions for the Elderly (Instituição de Longa Permanência - ILPI in Portuguese). Chronic comorbidities increase the demands of health care and generate situations that can be managed by the PMC caregiver. Population aging requires the planning of strategies and public policies aimed at providing continuous care for the older adults, including those living in communities. The PMC emerges as an intersectoral alternative to assist in this issue. CONCLUSIONS The PMC can be considered a good practice model to be expanded to other locations, however there are gaps that need to be rediscussed so that its processes are improved and its results enhanced.